Socioeconomic Disparities in Diagnostic Testing after Positive Aneuploidy Screening - Wong, Amy E.; Dungan, Jeffrey; Feinglass, Joseph; Grobman, William A. (American Journal of Perinatology, 2015)
Objective The objective of this study was to investigate the association between type of health insurance (Medicaid vs. private) and uptake of diagnostic testing for fetal aneuploidy after a positive screening test result.Methods We performed a retrospective cohort study of pregnant women who underwent aneuploidy screening in the first and/or second trimesters of pregnancy and received positive results. The characteristics of and outcomes for women with Medicaid were compared with those of women with private insurance in both univariable and multivariable analyses.Results In this study, 75 women with Medicaid and 75 with private insurance were analyzed. Those with Medicaid were younger (33.8 vs. 36.9 years, p < 0.01), and more likely to be of non-white race/ethnicity (88 vs. 27%, p < 0.01), unmarried (65 vs. 19%, p < 0.01), non-English speaking (12 vs. 0%, p < 0.01), and multiparous (76 vs. 59%, p = 0.02). They also were less likely to undergo diagnostic testing after a positive aneuploidy screen (35 vs. 57%, p < 0.01). In multivariable analysis, those with Medicaid remained significantly less likely to undergo diagnostic testing (odds ratio, 0.26; 95% confidence interval, 0.09–0.80).Conclusion Women with Medicaid are less likely than women with private insurance to undergo diagnostic testing after positive screening for aneuploidy. These results emphasize the potential importance of improved counseling for low-income women.
Keywords: prenatal diagnosis; socioeconomic disparities; aneuploidy; screening